Oxygen: Highlights from the Papers Published in the Journal up to February 2024 - John T. Hancock (Oxygen, 2024)
Oxygen (O2) was discovered approximately 250 years ago (Contribution 1), a breakthrough accredited to at least three people: Antoine-Laurent de Lavoisier in France (Antoine Lavoisier), Carl Wilhelm Scheele in Sweden, and Joseph Priestley in England [...]